Análisis del comercio justo y su impacto en la calidad de vida de los productores asociados a Fortaleza del Valle - Sánchez Santana, Yaritza Nathaly (2015)
The impact of fair trade in the quality of life of producers associated with Fortaleza del Valle was analyzed; we worked with four associations linked to the Corporation: Valles del Carrizal, La Fortaleza, Quiroga and Rio grande of Canuto, with a total of 930 partners. Data collection techniques were used as interviews and surveys, the sample was 272 producers. This research consisted of three stages; first a meeting with the manager, then selected SIISE socioeconomic indicators and the Superintendency of Popular and Solidarity Economy matrix was structured to survey the presidents of each association; in the second stage partners were surveyed to meet their socioeconomic status, the questionnaire was developed with the most relevant indicators of human, social and financial capital, the data were represented by diagrams radar to compare the situation of four partnerships. In the third stage results of interviews and surveys with the Principies of Good Living and the Popular Economy and Solidarity allow to analyzed the socio-economic impact on the positive and negative data that were identified linked eventually to solve the negative results with an action plan carried out to improve the socioeconomic management of the Corporación Fortaleza del Valle to its partners.